2022
DOI: 10.1038/s41398-022-02281-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of increasing levels of blood C-reactive protein on the inflammatory loci SPI1 and CD33 in Alzheimer’s disease

Abstract: Apolipoprotein ε4 (APOE ε4) is the most significant genetic risk factor for late-onset Alzheimer’s disease (AD). Elevated blood C-reactive protein (CRP) further increases the risk of AD for people carrying the APOE ε4 allele. We hypothesized that CRP, as a key inflammatory element, could modulate the impact of other genetic variants on AD risk. We selected ten single nucleotide polymorphisms (SNPs) in reported AD risk loci encoding proteins related to inflammation. We then tested the interaction effects betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Genetic diagnostics include, among others, the detection of polymorphisms of genes related to inflammatory complement activation, including CLU, CR1, SERPINA3, CRP, C2, CFH, C3, and C4. The polymorphism of their genes and the identified mutations of these genes may be a helpful complement to the diagnosis of inflammation in AD, significantly facilitating the work of clinicians [ 160 ]. Interdisciplinary research used in the diagnosis of inflammation should mutually confirm these results and complement each other [ 161 ].…”
Section: Diagnostics Of the Inflammatory Process In Admentioning
confidence: 99%
“…Genetic diagnostics include, among others, the detection of polymorphisms of genes related to inflammatory complement activation, including CLU, CR1, SERPINA3, CRP, C2, CFH, C3, and C4. The polymorphism of their genes and the identified mutations of these genes may be a helpful complement to the diagnosis of inflammation in AD, significantly facilitating the work of clinicians [ 160 ]. Interdisciplinary research used in the diagnosis of inflammation should mutually confirm these results and complement each other [ 161 ].…”
Section: Diagnostics Of the Inflammatory Process In Admentioning
confidence: 99%
“…Since the 1990s, researchers have demonstrated a significant presence of sustained inflammation in patients with AD (Aisen and Davis, 1994), confirmed by post-mortem tissues analysis (Gomez-Nicola and Boche, 2015). Epidemiological studies of largescale cohorts have shown that people showing enhanced pro-inflammatory proteins in the blood in mid-life are at higher risk of cognitive decline over the decades compared to subjects maintaining a low presence of pro-inflammatory factors in the blood (Leung et al, 2013;Huang et al, 2022). In addition, in their later life, these individuals are characterized by lower volume of brain with abnormal microstructure of white matter, increased myelin loss and the inability of the oligodendrocytes, the cells responsible for the production and maintenance of myelin, to repair myelin damages (Nasrabady et al, 2018;Collij et al, 2021).…”
Section: Role Of Inflammation In Ad: Clinical Datamentioning
confidence: 95%
“…Whereas populations with cognitive impairment also exhibit features of peripheral inflammatory activation, data from a cohort study of 2,479 patients ≥60 years of age in the United States showed that white blood cell counts (WBC), neutrophil counts, neutrophil-to-lymphocyte ratios, and neutrophil-to-albumin ratios in the peripheral blood of populations with cognitive impairment were significantly higher than those of normal populations ( Li W. et al, 2023 ). AD, the most prevalent neurodegenerative disease, has been reported to have enhanced genotypic effects of the proteins SPI1 and CD33 encoding proteins at the AD inflammation-related SNP locus as peripheral blood CRP levels increase, and an increased risk of conversion to AD in people with mild cognitive impairment (MCI) ( Huang J. et al, 2022 ). One study ( Lyu et al, 2023 ) demonstrated that by comparing diabetic (T2DM) patients aged 29–65 years who did not meet the criteria for a clinical diagnosis of cognitive impairment with the normal population (42.125 ± 10.436 years), although the difference did not gain statistical significance, the Montreal cognitive assessment scale (MoCA) scores of the T2DM patients showed a tendency to be lower than that of healthy controls and peripheral blood laboratory results showed significantly lower levels of peripheral blood IL-4 and brain-derived neurotrophic factor (BDNF) in the T2DM population compared to the healthy population.…”
Section: Peripheral Inflammation and Neurocognitive Impairmentmentioning
confidence: 99%